Postpartum glucose intolerance after gestational diabetes mellitus: tailored prediction according to data-driven clusters and BMI-categories - Lesniara-Stachon, Anna; Cosson, Emmanuel; Lacroix, Alain; Schenk, Sybille; Quansah, Dan Yedu; Puder, Jardena J. (Frontiers in Endocrinology, 2024)
Objectives To account for the heterogeneity of gestational diabetes (GDM), this study investigated tailored predictors during pregnancy and at 6-8 weeks postpartum of glucose intolerance (GI) at 1-year postpartum. We identified predictors according to data-driven clusters, analogous to the newly proposed diabetes classification, and for clinical ease also based on BMI-categories. Methods This is a secondary analysis of the MySweetheart trial. It included 179 women with GDM who underwent a 75g oral glucose tolerance test and HbA1c measurement at 1-year postpartum. Predictors were determined according to: a) cluster analysis based on age, BMI, HOMA-IR and HOMA-B; and b) BMI-categories (normal weight [NW], and overweight/obesity [OW/OB]). Results We identified two clusters during pregnancy and at 6-8 weeks postpartum (for both time points an “insulin-resistant”, and an “insulin-deficient” cluster). The “insulin-resistant” cluster was associated with a 2.9-fold (CI: 1.46-5.87; pregnancy) and 3.5-fold (CI: 1.63-7.52; at 6-8 weeks postpartum) increased risk of GI at 1-year postpartum. During pregnancy, the most relevant predictors of GI were history of previous GDM and fasting glucose for the “insulin-deficient” and NW category and HOMA-IR for the “insulin-resistant” and OW/OB category (all p ≤0.035). In the postpartum, predictors were more heterogenous and included the insulin-sensitivity-adjusted-secretion index and 1-h glucose in the “insulin-deficient” and NW women. Main conclusions In women with GDM, we identified “insulin-resistant” and “insulin-deficient” clusters with distinct risks of future GI. Predictors varied according to clusters or BMI-categories emphasizing the need for tailored risk assessments.